Uptake of oral fluid-based HIV self-testing among men who have sex with men and transgender women in Thailand. - Philippe Girault (Public Library of Science (PLoS), 2021)
Background Suboptimal uptake of HIV testing remains a primary bottleneck to HIV prevention and treatment for men who have sex with men (MSM) and transgender women (TGW) in Thailand. The World Health Organization has recommended HIV self-testing (HIVST) as an additional strategic HIV service. However, HIVST has not been fully endorsed and implemented in many countries in Southeast Asia. The aim of this study was to assess the uptake of oral fluid-based HIVST in MSM and TGW populations in Thailand. Methods During 2017 and 2018, we conducted a cross-sectional study using convenience sampling to enroll 2,524 participants from three major urban areas. Participants were recruited during outreach and online activities and were offered unassisted or assisted HIVST, or referral to HIV testing services. A descriptive analysis was performed for summarizing data. Results A total of 2,502 participants (1,422 MSM and 1,082 TGW) were included in the analysis with about one-third (36.1%) of them being first-time testers. Among all participants enrolled in the study, a total of 2,486 participants (99.3%) selected HIVST versus referral to HIV testing services. Of those who selected HIVST, 2,095 (84.3%) opted for assisted HIVST while the rest opted for unassisted HIVST: 1,148 of 1,411 MSM (81.4%) and 947 of 1,075 TGW (88.1%) selected assisted HIVST. While no serious adverse events were reported during the study, we found that among 179 participants who needed a confirmatory test and were referred to HIV testing services, 108 (60.3.4%) accessed these later services. Conclusions This study demonstrated a high uptake of oral fluid-based HIVST among MSM and TGW populations in Thailand and that HIVST could be scaled up through the national epidemic control program. However, a better understanding of HIV testing-seeking behavior and innovative follow-up solutions are needed to improve and monitor linkages to services for people who undertake HIVST.